Diferenciação morfológica e genética em populações de Croton muscicapa Müll. Arg. e Croton longibracteatus Mart. Gord. & de Luna (Euphorbiaceae) - Barbosa, Bárbara Laís Ramos (2017)
The present work consists in the specific delimitation study of Croton muscicapa Müll. Arg. and Croton longibracteatus Mart. Gord. & de Luna, belonging to Croton L., one of the biggest genus of Euphorbiaceae. It was analyzed the differentiation and the relations between these two species and associated morphotypes occurring along Espinhaço Range and adjacent areas in Brazil. For this purpose, samples of two species from herbarium were previously analyzed and 11 populations were collected, which correspond to five morphological groups, being used different methods of analysis. Morphotypes were tested by traditional uni and multivariated morphometrics involving 37 vegetative and floral variables. In addition, analyses of structuring and genetic variability using ISSR markers were realized, selecting the eight most variable primers and obtained 116 polymorphic loci. Foliar anatomy and micromorphology data was obtained from representatives of the 11 populations by optical and scanning electronic microscopy, respectively. Based on analyzed samples, it was observed that vegetative characters are much more variable than reproductive ones and are less taxonomically informative in this group. From the genetic point of view, the populations demonstrated high structuring and low variability. These different lines of evidence confirmed four distinct groups, two corresponding to C. muscicapa and C. longibracteatus, restricted to Chapada Diamantina and adjacent areas in Bahia, Brazil. Two new species are proposed (C. aemulus Barbosa & Carn.-Torres and C. graomogolensis Barbosa & Carn.-Torres), endemic to North of Minas Gerais. These species can be separated principally by limb indumentum, quantity and length of glands in the limb margin, length of pistillate and staminate flowers and amount of stamens. Croton aemulus corresponds to a natural hybrid, confirmed by the genetic pool shared between C. longibracteatus and C. graomogolensis. It is presented a recircumscription for C. muscicapa and C. longibracteatus, besides descriptions, key for identification, illustrations, photos, distribution maps and general comments for all species. The four species share anatomical and micromorphological characters, however, differs by the position of stamens, petiole surface, length of glands in the limb margin and quantity of secondary compounds. The two new species are considered as endangered, according to IUCN criteria.